Cosmology, teleology, and politics in Plato's Timaeus - Raunio, Salla (My University, 2022)
Plato’s Timaeus is generally considered as Plato’s cosmological dialogue. Interpretations often disregard the political context in which the cosmology is presented. In this thesis, I approach the Timaeusfrom a literary theoretical point of view. Such an approach implies that the dialogue is read as a whole in its historical context, and also any mentioned time and place, name or event of the frame story bears meaning. The dramatic event takes place at the time of Panathenaea, the biggest political festival in Athens. On the previous day, Socrates had given an account of the ideal state. On the next day, Socrates asks to hear speeches about what the philosophically trained guards of the ideal state would do and say in the case of war. Critias tells a story about Proto-Athens and its war against Atlantis. However, he only gives a summary of the story as Timaeus is given priority. The Timaeus thus consists of a summary of Socrates’ ideal state, a summary of Proto-Athens, and Timaeus’ cosmology. In this thesis, I set out to answer the following questions: Why does Plato present the cosmology in a political context along with two political accounts? How are the three accounts related to each other? I argue that the cosmology should not be read historically, as Critias does, but axiologically. The axiological reading enables political and ethical interpretation of cosmology. Timaeus’ teleological cosmology presents a paradigm for human behavior and ethical norms objectively realised in nature. I also argue that the cosmology offers interpretative tools to interpret the dialogue as a whole. Critias’ story presents a similarly structured, task-based constitution to Socrates’ ideal constitution. Proto-Athens set in the past and Socrates’ ideal state, projected in the future as a desired end, constitutes a teleological order.
Keywords: Plato, Timaeus, cosmology, teleology, politics